(untitled) (SAARC Journal of Agriculture, 2017)
An experiment was conducted under pot culture to investigate physiological responses as well as antioxidative enzymes activities that may lead to select sesame genotype (s) which were more waterlogging tolerant at vegetative stage. Four sesame genotypes viz. BD-6980, BD- 6985, BD-6992 and BD-7012 were grown under waterlogged (at vegetative stage) and control (no waterlogged) conditions. Plant height, root length, root volume, root dry weight and leaf area per plant in all the four sesame genotypes significantly decreased due to waterlogging at vegetative stage in comparison to controlled condition. Higher SPAD value (Soil and Plant Analyzer Development) and specific leaf mass were recorded in waterlogged plant than controlled plant during waterlogging period but reverse was the case during recovery period. All the genotypes showed positive indices of waterlogging tolerance in terms of better performance of root, stem, leaf and petiole. Among the genotypes, BD 6980 showed higher waterlogging tolerance in all the components followed by BD 6985. Malondialdehyde (MDA) content was found higher in waterlogged plant of all the four sesame genotypes in both waterlogging period and recovery period than the controlled plant. Antioxidant enzyme activities like Peroxidase (POD), Catalase (CAT), Ascorbate peroxidase (APX), Glutathione peroxidase (GPX) and Superoxide dismutase(SOD) were inconsistent in the present study but most of the antioxidant enzyme activities showed an increasing trend in waterlogged plant than that of control plant in all the genotypes. Comparatively low amount of MDA content and high antioxidant activities of sesame genotype BD 6980 is considered as highly tolerant to waterlogging and other three genotypes are moderately tolerant under water logging condition. SAARC J. Agri., 14(2): 31-45 (2016)